VIBRATION RESPONSE ANALYSIS OF FIVE-DEGREE-FREEDOM VEHICLE WITH STOCHASTIC STRUCTURAL PARAMETERS - JIA AiQin; JIANG ZhiQiang; CHEN JianJun; WEN ZhenHua (Jixie qiangdu)
In order to study effect that road roughness generated random excitation on the structural parameters of nonlinear vibration response of the vehicle system,random structural parameters of five- degrees-freedom nonlinear vehicle model were established,and the model parameters are considered as random variables,under the premise that between the tire and the body presence nonlinear spring to study the random vibration response of the model under random excitation. Road irregularity is considered to be a white noise process to establish the mechanical model,the nonlinear vehicle system was linearized by the energy difference method,a stationary covariance matrix for the random vibration responses was obtained by solving the Lyapunov equations,and the stable equivalent linear system parameters of vehicle were gained through iteration. The example calculation results show that this method can improve the accuracy and efficiency of computation.